Combined voltage and frequency control of a multi-area multisource system incorporating dish-Stirling solar thermal and HVDC link - Rajbongshi, Rumi; Saikia, Lalit Chandra (IET renewable power generation, 2018)
This study highlights the significance of dish-Stirling solar thermal system (DSTS) and high voltage direct current (HVDC) link in the combined automatic load frequency control (ALFC) and automatic voltage regulator (AVR) model of the multi-area thermal-diesel plant. Appropriate generation rate constraints and governor dead band for the thermal plant are considered. A maiden attempt has been made to apply fractional order integral double derivative controller with derivative filter (FOIDDF) as a secondary controller for both ALFC and AVR loops. The performance of the FOIDDF controller is compared with some commonly used classical controllers. The lightning search algorithm is implemented for simultaneous optimisation of the controller parameters. The comparison shows the better performance of FOIDDF than others. The effect of the AVR loop on the ALFC loop is also analysed for the first time in the combined model. The investigation of the effect of DSTS and HVDC links reveals that their inclusion improves the system dynamics. The superiority of the proposed controller has been established for variable insolation of the DSTS. The rigorous sensitivity analysis of the different position and magnitude of disturbance, change in tie-line synchronising coefficient and different condition of the DSTS reflects the robustness of the proposed controller parameters obtained at the nominal condition.